Determinação dos parâmetros astrofísicos dos aglomerados abertos NGC7193, NGC7772 e do objeto ESO442-SC04 - Mateus de Souza Angelo (2012)
In this work we determined the astrophysical parameters age, distance,interstellar reddening and membership for the open clusters NGC7193, NGC7772 and for the ESO442-SC04 object based on UBV (RI )cCCD photometry realized at OPD/LNA (Brazil). The B&C (IAGUSP) 0,6m telescope was used, with a field of view of 20'x 20' for NGC7193 and NGC7772 and of 10'x10' for ESO442-SC04. Observations were carried out during two nights on March/2008 and other two nights on September/2009. Adjacent regions to each of the targets were also surveyed and we collected 2MASS photometric data covering the same areas observed at OPD/LNA. We constructed color-magnitude diagrams (CMDs), color-color diagrams and also used a CMD decontamination technique. This technique is based on an algorithm that does a statistical comparison between the cluster CMDs and the control field CMDs, allowing a more rigorous distinction of the cluster and field populations and optimization of the isochrone fitting procedure. The structural parameters for the three targets were determined by fitting 2 and 3-parameter King profiles to the constructed radial density profiles. Theresults for the three targets are: NGC7772: log[t(yr)]=9.30 ±0.05, distance modulus (m - M )0=10.4 ± 0.3mag, distance d =1.2 ± 0.1kpc and reddening E(B - V )=0.039 ± 0.006mag. The structural parameters are: central density 0=0.8 ± 0.3 stars/arcmin2, background density bg =0.61 ± 0.07 stars/arcmin2 and core radius Rc=2.1 ± 0.8 arcmin. The target has an open cluster rem-nant (OCR) appearance with low-mass star depletion; NGC7193: log[t(yr)]=9.25 ± 0.05; (m - M )0 =9.4 ± 0.2mag, d = 759 ± 62pc and E(B - V )=0.049 ± 0.008mag. For the structural parameters we have obtained: 0=0.5 ± 0.2 stars/arcmin2, bg=1.05 ± 0.03 stars/arcmin2 e Rc =3 ± 1arcmin. The distance between the adopted central coordinates and the literature values is 1.7arcmin. The 13 likely members form an elongated structure, possibly due to a ruptureprocess along a preferential direction; NGC7193 CMDs also indicatelow-mass star depletion; ESO442-SC04: log[t(yr)]=9.50 ± 0.05; (m - M )0 =10.2 ± 0.1mag, d =1.1 ± 0.1kpc and E(B - V )=0.07 ± 0.02mag. The structural parameters are: 0=1.8 ± 0.5 stars/arcmin2, Rc=1.2 ±0.3 arcmin, tidal radius Rt=18 ± 6arcmin, concentration parameter c =log(Rt =Rc)=1.2 ± 0.2. ESO442-SC04 and NGC7772 are classfied as POCRs (Possible Open Cluster Remnants) and NGC7193 is classified as an open cluster. GMOS/GEMINI spectroscopic data present in the literature for 17 stars localized in the central region (5'x 5') of ESO442-SC04, jointly with CCD UBVRI photometry data obtained with the 4.1m SOAR Telescope (Cerro Pachón, Chile), showed that this target is not an OCR, but a fortuitous alignment of field stars. Our results, obtained with a four times larger observation area (10' x 10'), corroborate this conclusion when the isochrone fittings are compared. Results present in the literature for NGC7772 indicate 15 likely members, 10 of which are common to our 13 likely members sample. Within the uncertainties considered, the astrophysical parameters values obtained are inagreement with our analysis. For NGC7193, compared to the literature values, our results indicate a 2.7Gyr younger object, 321pc nearer to the Sun and submitted to a 0.019mag larger interstellar reddening. These differences are due to different metodological procedures adopted in the present study and in previous ones, mainly concerning the CMDs decontamination techniques used in each case.